Sustainable Luxury: Understanding Motivations for Consumer Purchase Decisions and Strategies to associate Brand Image with Sustainability - Agarwal, Manil (2011)
The luxury market is growing exponentially and gaining acceptance and increased demand around the world. At the same time the world is making attempts to achieve growth that is sustainable. This scenario means that luxury brands will soon have to adapt themselves to ensure that their expansion and product development aims to achieve highest levels of sustainability. But before entering the market segment of sustainable luxury, brands need to understand the motivations that influence the consumers’ purchase decisions to make the right marketing decisions. Also they will have to develop strategies that will associate their brand image with sustainability.